Strategies for Improving Computer Science Students’ Academic Performance in Programming Skill - Akinola Kayode Emmanuel; Olanrewaju Grace Oluwadamilare; Oyenuga Augustine Yomi (Current Topics on Mathematics and Computer Science Vol. 4, 2021)
Programming dexterity is a necessary skill for computer science students. Teaching and learning programming concepts and abilities, on the other hand, has been identified as a significant challenge for both teachers and students. As a result, developing effective learning methodologies and environments for programming courses has become a major topic. The goal of the study is to suggest improvement strategies for effectively teaching Computer Programming to undergraduate students in the field of computer science and information technology. Computer programming is widely thought to be one of the most challenging courses in tertiary institutions since it is too abstract and demands better analytical and problem-solving capabilities. The study employed a survey research design. The study used a descriptive method, actual student grades, and informal interviews among lecturers. According to the recognised evaluation findings, 47% of students in the programming course exhibit inadequate academic performance. This led to the conclusion that there is a need for improvement strategies that need planning and implementation in order to increase students’ motivation to study, academic performance, and education quality in the subject of computer science. Relevant and effective recommendations were proposed.